2013
DOI: 10.1097/brs.0b013e31827ec51f
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Steroid Injections Are Associated With Less Improvement in Patients With Lumbar Spinal Stenosis

Abstract: Summary of Background Data Lumbar spinal stenosis is a common incidental finding among adults over the age of 60, The use of ESI in these patients is common, although there is little evidence in the literature to demonstrate the long-term benefit of ESI in the treatment of lumbar stenosis. Objective The hypothesis of this study was that patients who received epidural steroid injections (ESI) during initial treatment as part of the Spine Patient Outcomes Research Trial (SPORT) would have improved clinical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 36 publications
(33 reference statements)
2
26
2
6
Order By: Relevance
“…Similar to our findings, a study by Radcliff et al found no difference in baseline SF-36 outcomes scores between injected and noninjected patients. 12 Postoperatively (averaged over a 4-year period), they found patients treated with injections had nearly an 8-point lower magnitude of improvement in SF-36 physical function scores than noninjected patients. Although we found that the postoperative SF-12 PCS score was lower in the injection group, the group also had lower preoperative PCS scores and the actual improvement in PCS scores did not differ between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, a study by Radcliff et al found no difference in baseline SF-36 outcomes scores between injected and noninjected patients. 12 Postoperatively (averaged over a 4-year period), they found patients treated with injections had nearly an 8-point lower magnitude of improvement in SF-36 physical function scores than noninjected patients. Although we found that the postoperative SF-12 PCS score was lower in the injection group, the group also had lower preoperative PCS scores and the actual improvement in PCS scores did not differ between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Radcliff et al 10 reported that ESIs were associated with signifi cantly less improvement during 4 years' follow-up in patients treated either surgically or nonoperatively for lumbar spinal stenosis. In several studies, detrimental complications after epidural steroid injections have been reported, such as infections, bleeding and spinal cord injuries, although the incidence is very low.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation of our study was the shorter follow-up of just 6 months compared with 4 years in the SPORT. However, Radcliff et al 10 reported the differences in outcome at regular time-points during 4-year period, and according to the fi gure in their publication, the negative effect of ESIs on improvement in both the surgical and nonoperative groups was already noticeable after 6 months. A third limitation of the present study is the small number of patients in the nonoperative treatment group, limiting the precision of the results and potentially leading to a type II error (failure to reject a false null hypothesis).…”
Section: ➢ Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical indication for lumbar stenosis is still controversial, and the criteria are not always clear. More recent studies [4][5][6][7][8] question the real efficacy of the procedure, and whether the results significantly improve the quality of life of the patients. It is difficult to compare the improvement of patients objectively following surgery, given that even after considerable decompressions, some patients continue to present symptoms.…”
Section: Introductionmentioning
confidence: 99%